What Does Brazil Know about the Origin and Uses of Tree Species Employed in the Housing Sector? Perspectives on Available Species, Origin and Current Challenges - De Araujo, V. [UNESP]; Vasconcelos, J. [UNESP]; Gava, M. [UNESP]; Christoforo, A.; Lahr, F.; Garcia, J. (Commonwealth Forestry Association, 2021)
HIGHLIGHTS Outcomes with low margins of error are useful for the development of strong forest policies. Native origin timber remains a complex issue and requires efforts to improve clarity. Native timber comprises a significant part of the timber housing sector in Brazil. Exotic timber is used widely throughout the domestic construction industry. In terms of timber housing in Brazil, eucalypt wood is less used than pine. SUMMARY Timber consumption is a complex discussion for the industry, in part because the issue has been marked by doubts about lineage and origin. This paper aimed to identify challenges related to species, origins and wood use in the Brazilian construction sector. Searches on corporate websites and face-to-face interviews were used to identify involvement by species and origin in the domestic production of timber for housing. Relevant results were obtained for both methods since their margins of error were low. Forty exotic and nine native species were revealed to contribute significantly to the construction sector. ‘Grapia' and ‘Angelim pedra' native woods and eight eucalypt and pine species were shown to be the most popular through both methodologies. Pine timber was found to be in greater demand than that of Eucalyptus species. Despite some lack of clarity relating to the origin of certain species, the sector's status was better than expected. However, it still requires assertive actions to increase the use of legalized wood in order to favour product certification and integration into foreign markets. .
Keywords: construction; exotic wood; native wood; survey; timber housing